Multi-modality imaging in the diagnosis of fetal vascular ring - Weinberger, Sharon; Cartoski, Mark (Prenatal Cardiology, 2022)
Prenatal diagnosis of vascular ring can improve the time to intervention. Correlation of fetal diagnosis with postnatal imaging in the newborn period is needed for appropriate clinical management, surgical referral, and surgical approach if indicated. We present a case of a fetal diagnosis of double aortic arch with postnatal feed and swaddle cardiac MRI diagnosis of right aortic arch and aberrant left subclavian artery.